(untitled) (Acta Scientiarum. Education, 2018)
This article emerges from an exploratory qualitative study conducted with faculty members from higher education institutions in Brazil, Spain and Mexico. The goal of the study was to analyse the perceptions of faculty members from the looked at institutions, on pedagogical innovation resulting from the use of Information and Communication Technologies (ICT) in their teaching practices. The data were collected through a semi-structured questionnaire forwarded by e-mail. Content analysis technique was used to study the data. Results showed three types of perceptions held by faculty members in relation to pedagogical innovations arising from the use of ICT in their practices. Most firmly believe and identify innovations resulting from the use of ICT. A smaller number of participants also identify innovations, but point out that, in addition to the use of ICT, they are the result of the teacher’s attitude. There is also the opinion related to the saturated use of ICT, without the perception of innovation.